A ética da vida - Edgard de Carvalho Assis (EccoS – Revista Científica)
A future ethics must be included two preliminary tasks: the highest knowledge degree as a consequence of how we act and elaborate a transdiciplinar knowledge, that is able to match factual and axiomatic knowledge. Such ethics must be understood as a new public philosophy, a great number of values and cultures constantly fed with dialogy between science and tradiction, between real and imaginary, between subjectivity and objectivity, between East and West. It must be founded in na egocentric perspective, balanced from which if it will be able and if it will owe to think the relationship among human being nature, human being world, like as a permanent and necessary uniduality.